2020
DOI: 10.3390/app10207349
|View full text |Cite
|
Sign up to set email alerts
|

AR Book-Finding Behavior of Users in Library Venue

Abstract: ARKit and ARCore, key technologies in recent augmented reality (AR) development, have allowed AR to become more integrated in our lives. However, how effective AR is in an auxiliary role in venue guidance and how to collect the actual behaviors of users in physical venues are worth exploring. This study used navAR, a spatial behavior analysis system app that our research team developed, to collect the actual behaviors of participants in physical space via a smartphone, such as time, distance travelled, and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The product developed by researchers is AR-Book-based science learning media with Problem Based Learning model. AR-Book is a combination of ordinary books with AR technology (Lee et al, 2020). The form of Augmented Reality media development refers to the results of previous research, namely the results of Iskandar and Mayarni's research entitled "Development of Augmented Reality Media on the Introduction of Planets and Celestial Bodies for Elementary School Science Learning".…”
Section: Results Of Ar-book Based Science Learning Media Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The product developed by researchers is AR-Book-based science learning media with Problem Based Learning model. AR-Book is a combination of ordinary books with AR technology (Lee et al, 2020). The form of Augmented Reality media development refers to the results of previous research, namely the results of Iskandar and Mayarni's research entitled "Development of Augmented Reality Media on the Introduction of Planets and Celestial Bodies for Elementary School Science Learning".…”
Section: Results Of Ar-book Based Science Learning Media Developmentmentioning
confidence: 99%
“…Researchers created AR-Book-based science learning materials using a problem-based learning approach. An AR-Book combines traditional books with augmented reality technology (Lee et al, 2020;Tomi et al, 2013). Researchers developed AR-Book learning media using the Assemblr EDU application.…”
Section: Development Of Augmented Reality Learning Media Bookmentioning
confidence: 99%
“…In recent years, AR technology has been used not only as an aid but also a research analysis tool. Lee et al [1] developed the AR behavior analysis system navAR to understand the differences between the AR-aided book-searching behavior and the general book-searching behavior of library users [2].…”
Section: Benefits Of Armentioning
confidence: 99%
“…The system records user behavior and then automatically uploads it to the cloud for analysis. The system has been applied to a library AR book-searching experiment, the results of which revealed that with the aid of AR, the book-searching paths of users are more directed [2]. To understand whether gamified processes possess potential guidance functions for AR guide systems, the researchers developed an AR navigation app (Appendix A) for the Greater Taipei Biennial of Contemporary Art 2020 exhibition, "Authentic World", which was held by the Yo-Chang Art Museum in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Dünser et al [8] compared three forms of navigation: mobile AR, digital map, and mobile AR+ digital map, the behavioral experiment showed no significant differences in navigation efficiency between the three, but users preferred the mobile AR+ map form of navigation. Lee et al [9] developed a mobile AR navigation application for libraries: navAR. By comparing it with text-based navigation, they found that AR navigation has good usability and makes users' book-finding behavior more regular and faster.…”
Section: Introductionmentioning
confidence: 99%